2012
DOI: 10.1111/j.1365-2656.2012.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric reproductive interference between specialist and generalist predatory ladybirds

Abstract: Summary1. Closely related species often differ greatly in the quality and breadth of resources exploited, but the actual mechanisms causing these differences are poorly understood. Because in the laboratory specialized species often survive and perform as well or better on host species that are never utilized in nature, negative ecological interactions restricting host range must exist. Here, we focused on reproductive interference, which has been theoretically predicted to drive niche separation between close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 59 publications
0
61
2
Order By: Relevance
“…Theoretical studies (Ribeiro and Spielman 1986;Kuno 1992) have opened our eyes to the ecological importance of reproductive interference. Recent empirical studies Takakura et al 2009;Crowder et al 2010;Takakura and Fujii 2010;Noriyuki et al 2012) have convinced us that reproductive interference exists broadly in many taxa at the individual level. The next advance in this theme requires more empirical studies conducted in the field at population level.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Theoretical studies (Ribeiro and Spielman 1986;Kuno 1992) have opened our eyes to the ecological importance of reproductive interference. Recent empirical studies Takakura et al 2009;Crowder et al 2010;Takakura and Fujii 2010;Noriyuki et al 2012) have convinced us that reproductive interference exists broadly in many taxa at the individual level. The next advance in this theme requires more empirical studies conducted in the field at population level.…”
Section: Discussionmentioning
confidence: 98%
“…These predictive works have encouraged empirical studies. Now we have many examples of reproductive interference for a broad range of taxa: insects Kishi et al 2009;Noriyuki et al 2012), mites (Fujimoto et al 1996;Takafuji et al 1997), amphibians (Hettyey and Fig. 6 Results of nonmetric multidimensional scaling (NMDS) analysis of ISSR data from nine populations of V. p. lilacina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When mating takes place on or near the host plant, the plant serves not only as food for the offspring but also as a mating site (e.g., Feder et al 1994). Therefore, reproductive interference may drive host partitioning among closely related species, creating spatial segregation of mating sites (Colwell 1986;Kuno 1992;Noriyuki et al 2012;Friberg et al 2013;Kishi and Tsubaki 2014;Noriyuki 2015). However, whereas some empirical studies have suggested the causal role of reproductive interference in the evolution and/or maintenance of host-plant partitioning as well as microhabitat partitioning, there is a need for modeling studies to address whether reproductive interference can indeed drive the evolution of host-plant partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…However, enormous numbers of alien species are known to create severe problems worldwide. Increasingly results of numerous empirical studies have also suggested that reproductive interference is biased or rather one-way [8,9,[14][15][16][17]. The extent of the bias of the reproductive interference between the alien and native species might provide a key to explaining the invasion speed of alien species.…”
Section: Introductionmentioning
confidence: 99%